An international survey of healthcare workers use of personal protective equipment during the early stages of the COVID‐19 pandemic. Issue 2 (26th March 2021) - Kea, Bory; Johnson, Alicia; Lin, Amber; Lapidus, Jodi; Cook, Jennifer N.; Choi, Calvin; Chang, Bernard P.; Probst, Marc A.; Park, Joel; Atzema, Clare; Coll‐Vinent, Blanca; Constantino, Giorgio; et al.
Abstract: Objective: Little is known regarding the specific ways personal protective equipment (PPE) has been used and reused during the coronavirus disease 2019 (COVID‐19) pandemic. The objective of this study was to evaluate the patterns of PPE use and the impact of PPE availability on the attitudes and well‐being of an international population of healthcare workers. Methods: This was an online, cross‐sectional survey of healthcare workers. The survey was disseminated internationally using social media, specialty society list‐serves, and email augmented by snowball sampling to healthcare workers who provided direct care to patients with suspected or confirmed COVID‐19. The survey was conducted between April 13 and May 1, 2020. The primary outcome was self‐reported PPE use during aerosol‐generating medical procedures. Other outcomes included PPE use during care for respiratory patients in general, PPE reuse, PPE decontamination, and healthcare worker impressions related to their work and the pandemic. Results: A total of 2227 healthcare workers from 23 countries completed the survey. The N95 was the most common respirator among the 1451 respondents who performed aerosol‐generating procedures (n = 1050, 72.3%). Overall, 1783 (80.1%) of providers reported general reuse of PPE, which was similar across US regions but less common in Canada, Italy, and Spain. The most commonly reused item of PPE was the N95 respirator, with the majority of respondents who reused PPE reporting N95 reuse (n = 1157, 64.9%). Of the 1050 individuals who wore an N95 mask while performing an aerosol‐generating medical procedure, 756 (72%) reported re‐using an N95, and 344 (45.5%) reported reuse for >3 days. Qualitative results identified several common themes, including (1) lack of availability of PPE, (2) fear and anxiety as a result of inadequate PPE, (3) potential exposure to family members, and (4) concerns regarding workload and pay. Conclusions: This international survey of healthcare workers found that N95 respirators were commonly used to care for patients with respiratory symptoms with and without aerosol‐generating medical procedures. Healthcare workers reported an unprecedented need to reuse PPE that was designed for single‐use, specifically the N95 respirator. The reuse of PPE increased the perceived risk for COVID‐19 infection and harmed mental health.